Analysis of Problem Based Learning Model on Students' Cognitive Intelligence in Mathematics Class IV Elementary School - Wardathi Khuzaifah; Mhmd Habibi; Risna Wati (Journal of Educational Sciences, 2023)
The primary objective of this study is to investigate the impact that the PBL learning paradigm has on the cognitive ability of pupils. Quantitative techniques and experimental approaches are used in this kind of study. This design is a quasi-experimental one with a nonequivalent control group. SDN 111 pupils make up the whole population of this area, which has a total of 300 individuals. SDN 111 Pekanbaru provided the samples, which consisted of 25 pupils from class IV A and 25 students from class IV B. The method of sampling is called probability sampling, and it is combined with plain random sampling. The instrument is a description exam questions. The findings of the research using the independent sample t test demonstrate that Tcount = 2.840 and Ttable = 2.007, where Tcount is bigger than Ttable (2.840 > 2.007). Given these findings, we may conclude that H1 is correct and H0 is incorrect. To summarize, the implementation of the PBL model has a positive impact on the level of cognitive intelligence exhibited by primary school children.